Formação inicial e concepções de assistentes sociais do interior do Rio Grande do Norte sobre a sexualidade da pessoa idosa - Silva, Carla Bessa da [UNESP] (2015)
The fast and continuous growth of the elderly population all over the world, including Brazil, has been establishing a new scenery in the contemporary society. The aging of the population brings consequences to the society in general; therefore it has to be able to provide a better life quality to the elderly population. Considering, among other aspects, the need of usufruct and experience on sexuality. Therefore, it is necessary capable professionals to deal with this specific group, including also the presence of the social worker. Thus, this following research, of a descriptive impress and qualitative nature, has had a goal to investigate the initial formation and the conceptions of the social workers from the county of Pau dos Ferros / RN, about Sexuality and Sexual Education, focusing on checking how they receive the sexuality of the elderly people and how they deal with the formation / information regarding sexual education focused on this group of people. So, we have delimitated for an interview the site Social Assistance Reference Centers (CRAS), for we believe that it is in this place that the strengthening of familiar and communitarian bounds is promoted, including the elderly people. The research has had the support of six social workers, who responded to a semi-structured survey containing sixteen opened questions, which were recorded and transcripted in full. Following a qualitative way, the data analysis was based on the content analysis. The results have showed us that in some moment of the formation on the graduation of the social workers, they had contact with the sexuality theme. Despite that, they have reported difficulties in their professional practice when it comes to bringing this subject up with the groups of acquaintanceship of elders, showing that the contact with this subject had been superficial. As for the conceptions found by these professionals we could see ...